Foreign Layer of the Chuvash Book - Alena M. Ivanova; Eduard V. Fomin (Publishing house "Sreda", 2020)
The article is devoted to the consideration of extraterritorial publications on the Chuvash theme. The purpose of the work is to identify the essential features of the foreign layer of the Chuvash book. The conclusions of the work are based on a quantitative and qualitative analysis of bibliographic indexes and a direct study of the books themselves de visu. The authors of the article consider foreign books as an important component of modern Chuvash culture, endowed with communicative, cognitive-cumulative, ethno-presentative and educational functions. Extraterritorial editions of the Chuvash book appeared in the first half of the 19th century, and only by the end of the 20th century they formed an independent layer. At the same time, one should objectively speak of two exteriorics - the Chuvash and by the poet G. Aygi. Each of them is represented by almost 150 publications. The predominant problematic of the foreign language layer of the Chuvash book proper is the Chuvash language. Moreover, its notable aspect is the publication of books in the Chuvash language or their publication with parallel texts in Sweden and Turkey. G. Aygi's foreign publications are already represented by collections of poems in Russian, published by the publishing house of the artist N. Dronnikov in France. This work is a publication that should provide an introduction to the scientific use of literature that has not yet become the property of the Chuvash Studies. Its task is to promote the full functioning of modern Chuvash science in conjunction with the world one. The authors come to the conclusion that, in general, the foreign layer of the Chuvash book has an enduring value, and many of the scientific publications published in the past are rightly elevated to the rank of classical ones by the scientists.